Vaikkam satyagraha and Gandhi - Ravindran, T. K. (Monograph series - Sri Narayana Institute of Social and Cultural Development ; no. 1., 1975)
On the 1924-25 sociopolitical agitation mounted by the Indian National Congress to achieve a just social status for underprivileged classes.